The impact of selective heuristic program to alleviate aggressive behavior of Elementary Students - Adil, Jihan S.; Hasan, Nihad O. (Humanities Journal of University of Zakho, 2018)
Aggressive behavior is a wide –spread phenomenon in our region which causes fear, concern and depression among our youth as result of the conflicts and tension which face the region. Thus, this phenomenon should be tackled scientifically to restore peace and stability and establish normal relations among people. This study aims to; 1- Design an instructional program to handle aggressive behavior among ninth grade pupils. 2- ldentify the effect of this program in handing aggressive behavior among pupils. The study tries to verify the following nil hypothesis; There are statistically significant differences between the mean scores of the experimental group and the control group on the scale of aggressive behavior after implementing the instructional program. To test the hypothesis, the researchers used au experimental group and control group with a pre and posttest .The sample consisted of 20 pupils randomly divided into two groups which they are experimental group and control group. The researchers designed the following; An instrument to measure aggressive behavior of 42 items.The instrument was assessed for face validity and reliability. Reliability was measured by split- half (0,87 ). An instructional programme based on planning, programming and budget and it included 14 sessions. The results showed that the instructional programmed had an effect on minimizing aggressive behavior among pupils. The researchers suggested some suggestions and recommendations in the light of the results.